A generic approach of polishing metals via isotropic electrochemical etching. (March 2020) - Yi, Rong; Zhang, Yi; Zhang, Xinquan; Fang, Fengzhou; Deng, Hui
Abstract: Isotropic etching polishing (IEP), which is based on the merging of hemispherical holes that are formed by isotropic etching, is proposed in this study as a universal metal finishing approach. Modeling of the surface evolution during IEP is also carried out, and the formation of a metal surface is predicted. The etching anisotropy of titanium is experimentally studied, and the results show that isotropic etching can be realized under optimized conditions. Isotropic etching sites originate from a breakdown of the passivation layer. Both the density and growth rate of the holes are affected by the current, and a large etching current is preferred for the realization of highly efficient polishing. IEP has been shown to be effective and efficient for surface finishing of TA2. The surface Sa roughness is drastically reduced from 64.1 nm to 1.2 nm, and a maximum polishing rate of 15 μm/min is achieved under an etching current of 3 A. IEP has also been successfully applied for surface finishing of other metals, including TC4, stainless steel 304, aluminum alloy 6063 and pure nickel, demonstrating that IEP can be considered a universal approach for finishing metals. Graphical abstract: Image 1 Highlights: Isotropic etching polishing (IEP) was proposed as a general metal finishing approach. Isotropic electrochemical etching of titanium with ultrasmooth inner surface was realized. Sa roughness of TA2 was reduced from 64.1 to 1.23 nm with a maximum MRR of 15 μm/min. IEP was effective for surface finishing of stainless steel, aluminum and nickel.